2020
DOI: 10.3390/ma13215036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Boric Acid Corrosive Environment on the Microstructure and Properties of Concrete

Abstract: Boric acid, a weak acid, is often used to shield neutrons in water cooling systems in nuclear power stations. The leakage of boric acid in water cooling systems damages the concrete structure and affects the safety of nuclear power engineering. In this experiment, concrete specimens were cured with boric acid at 20, 40, and 70 °C to study the effect of boric acid on the microstructure and properties of concrete. X-ray diffraction (XRD) and thermogravimetry and differential scanning calorimetry (TG-DSC) were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The effect of borate on the hydration of different cementitious phases had been studied over the past three decades. These studies indicated that [21,23,27,[38][39][40][41][42]:…”
Section: General Characteristics Of Concentrates and Their Problematic Naturementioning
confidence: 99%
“…The effect of borate on the hydration of different cementitious phases had been studied over the past three decades. These studies indicated that [21,23,27,[38][39][40][41][42]:…”
Section: General Characteristics Of Concentrates and Their Problematic Naturementioning
confidence: 99%
“…Boron-containing compounds such as borates and boric acid control the corrosion of steel embedded in concrete 36 , 37 . However, many researchers have reported either negligible or, in many cases, deteriorating effects of boron-based compounds added to concrete on the properties of concrete and reinforcement bars 38 – 41 . The inhibitory effects of boron-based compounds on iron and steel can be attributed to their pH-buffering action 42 – 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Sulfates in groundwater are usually of natural origin but can also come from fertilizers and industrial wastewater. As the author states in [23,24], the progress of sulfate corrosion depends on the type of cation associated with the sulfate anion and on the salt concentration. The most aggressive chemical compounds include the salts of the following types: CaSO 4 , Na 2 SO 4 , K 2 SO 4 , MgSO 4 , (NH 4 ) 2SO 4 , and acid-H 2 SO 4 .…”
Section: Introductionmentioning
confidence: 99%